2014
DOI: 10.1371/journal.pone.0110336
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Selenium in Stranded Indo-Pacific Humpback Dolphins and Implications for Their Trophic Transfer in Food Chains

Abstract: As top predators in the Pearl River Estuary (PRE) of China, Indo-Pacific humpback dolphins (Sousa chinensis) are bioindicators for examining regional trends of environmental contaminants in the PRE. We examined samples from stranded S. chinensis in the PRE, collected since 2004, to study the distribution and fate of total mercury (THg), methylmercury (MeHg) and selenium (Se) in the major tissues, in individuals at different ages and their prey fishes from the PRE. This study also investigated the potential pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…2): all Hg concentrations in liver from sharks exceeding 2.6 m PCL for males and 2.8 m PCL for females were higher than those in muscle. The marked increase in hepatic Hg concentrations after maturation may be explained by the continuous intake of Hg via their diet and the reduction in growth at maturation, as well as the formation of Hg-Se complexes (Storelli and Marcotrigiano, 2002;Endo et al, 2002Endo et al, , 2006Endo et al, , 2013Lailson-Brito et al, 2012;Karimi et al, 2013;Gui et al, 2014). In agreement with our definition of mature males (exceeding 2.6 m PCL) and females Wintner and Dudley (2000) report that the 50% maturities for males and females to be 2.50 and 2.74 m PCL, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…2): all Hg concentrations in liver from sharks exceeding 2.6 m PCL for males and 2.8 m PCL for females were higher than those in muscle. The marked increase in hepatic Hg concentrations after maturation may be explained by the continuous intake of Hg via their diet and the reduction in growth at maturation, as well as the formation of Hg-Se complexes (Storelli and Marcotrigiano, 2002;Endo et al, 2002Endo et al, , 2006Endo et al, , 2013Lailson-Brito et al, 2012;Karimi et al, 2013;Gui et al, 2014). In agreement with our definition of mature males (exceeding 2.6 m PCL) and females Wintner and Dudley (2000) report that the 50% maturities for males and females to be 2.50 and 2.74 m PCL, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Marine predators, particularly long-lived species such as sharks, tuna, swordfish, and cetaceans, accumulate high levels of mercury (Hg) via the food web, and the hepatic Hg concentration in marine cetaceans is greater than the Hg concentration in the muscle (Honda et al, 1983;Andre et al, 1991;Holsbeek et al, 1998;Zhou et al, 2001) as the hepatic Hg concentration increases greatly after maturation due to the formation of Hg-Se complexes (Endo et al, 2002(Endo et al, , 2006Lailson-Brito et al, 2012;Karimi et al, 2013;Gui et al, 2014). In contrast to cetaceans, there are only limited data available on Hg concentration in the shark liver because most Hg surveys on shark species were undertaken for the edible part of the muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low percentage of the methylated fraction of total Hg found in the tissues of juvenile whales suggests ( Supplementary Tables S1 and S2 ), that the detoxification process is fully developed from the early age of the animals, which is in contradiction with previous suggestions that young animals are not able to efficiently demethylate MeHg 29 . Additionally, several authors 30 31 suggested that initiation of a demethylation process requires the total Hg concentration to exceed a certain threshold value. In striped dolphin, the threshold value was suggested to be 0.49 μmol of total Hg kg −1 of wet weight of liver 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been shown in studies in a variety of species, including marine mammals (Cuvin-Aralar and Furness, 1991;Frodello et al, 2000;Gui et al, 2014;Sakamoto et al, 2013) exposed to these elements for a long time, even before the industrial period (Holsbeek et al, 1998). Thus, several mechanisms for resistance to the adverse effects of Hg have been proposed.…”
Section: Introductionmentioning
confidence: 89%